A Randomized, placebo-controlled crossover study to evaluate postprandial glucometabolic effects of mulberry leaf extract, vitamin D, chromium, and fiber in people with type 2 diabetes - Mohamed, Mafauzy; Zagury, Roberto Luis; Bhaskaran, Kalpana; Neutel, Joel; Mohd Yusof, Barakatun Nisak; Mooney, Linda; Yeo, Lihe; Kirwan, Bridget-Anne; Aprikian, Olivier; von Eynatten, Maximilian; Johansen, Odd Erik (Springer Healthcare, 2023)
Introduction: Reducing postprandial (PP) hyperglycemia and PP glucose excursions is important for overall glycemic management. Although most therapeutic lifestyle interventions that reduce caloric intake would affect this, there is no particular nutritional intervention favored. Methods: We evaluated the effects of a novel natural food adjuvant combining mulberry leaf extract (MLE) with other bioactive ingredients, in people with type 2 diabetes (T2D) originating from Asia, on improving PP glucometabolic response in a randomized controlled exploratory crossover, two-center study (USA, Singapore). A 2-g blend of 250 mg MLE containing 12.5 mg of 1-deoxynojirimycin (DNJ), fiber (1.75 g), vitamin D3 (0.75 ¼g), and chromium (75 ¼g), compared with a similar blend without the MLE, was sprinkled over a 350-kcal breakfast meal (55.4 g carbs) and PP blood glucose (primary exploratory endpoint), insulin, and incretin hormones (GLP-1, GIP) were evaluated in blood samples over 3 h. Changes in incremental areas under the concentration curve (iAUC) and maximum concentrations (Cmax) were compared. Results: Thirty individuals (12 women, mean age 59 years, HbA1c 7.1%, BMI 26.5 kg/m2) were enrolled and the MLE-based blend relative to the blend without MLE significantly reduced glucose iAUC at 1 h (ˆ’ 20%, p < 0.0001), 2 h (ˆ’ 17%, p = 0.0001), and 3 h (ˆ’ 15%, p = 0.0032) and Cmax mean (95% CI) difference ˆ’ 0.8 (ˆ’ 1.2, ˆ’ 0.3) mmol/L, p = 0.0006. A statistically significant reduction in 1 h insulin iAUC (ˆ’ 24%, p = 0.0236) was observed, but this reduction was no longer present at either 2 h or 3 h. No difference in GLP-1 was seen, but GIP response (iAUC and Cmax) was less with the MLE-based blend. Conclusions: The observation of a significant glucose reduction paralleled with a significant lower insulin response supports a reduced gastrointestinal glucose absorption. These results support the use of a 2-g natural blend of MLE, fiber, vitamin D, and chromium in T2D as a convenient dietary adjuvant to improve PP glucometabolic response. ClinicalTrials.gov identifier NCT04877366.